Damage in MMCs and its role in microstructural design - Lahaie, Denis J.G. (My University, 1998)
Metal-matrix composites (MMCs) have potential as load bearing components for particular functional requirements. However, MMCs are more difficult to form than conventional metals and alloys due to the tendency of suffering microstructural damage at low plastic strains. It is thus of importance to understand the forms of microstructural damage, its level and spatial distribution. In this work, three main areas of investigation related to damage accumulation in MMCs were considered: the hydrostatic extrusion of MMCs, a theoretical investigation of scale effects in MMCs and plane strain compression experiments on model composites to study load transfer and fibre distribution effects on the patterns of plastic flow in the matrix. In the experiments on the hydrostatic extrusion of particulate MMCs, it was found that damage occurred in the form of reinforcement cracking, that the amount of damage varied linearly with applied plastic strain and that the rate of damage accumulation depended on the morphology of the reinforcement. The extrusion process was examined in regard to its ability to limit or suppress damage through the action of high compressive hydrostatic pressures. A slip-line field analysis was adopted to relate the effect of process parameters such as the amount of reduction and die angle to the magnitude and distribution of hydrostatic pressure in the extrusion dies. The linear relationship between damage and applied plastic strain was explained using a micro-mechanical description of the response of MMCs to plastic flow and the effect of microstructural variables such as volume fraction, shape and size of the reinforcement on the rate of damage accumulation was discussed. In addition, the tensile properties of MMCs subsequent to hydrostatic extrusion were quantified and the effect of previous extrusion was described in terms of the strain hardening of the matrix materials and the damage accumulation in the reinforcement materials and their influence on the stability of the plastic flow process. In the work on plane strain compression of model composites, the effect of reinforcement distribution on the pattern of flow in Cu-W MMCs was described using maps of equivalent strain obtained from the analysis of deformed surface grids. The level and distribution of strain was found to be related to the spatial distribution of the reinforcements. The fiber distribution also influenced the efficiency of the fibers as obstacles to macroscopic flow. Comparison of the results with numerical analyses allowed a link to be established between the observed damage mechanism of decohesion and the state of stress and local strain level in the composite. An optical method was used to get information on the load transfer process in a Cu-sapphire MMC plastically deformed in plane strain compression. The fracture of the sapphire fiber was related to the measured stress state. In the theoretical analysis of scale effects in MMCs, scale dependent bounds on strength were developed and scale dependent composite design charts were constructed. The results highlighted the importance of the scale of the reinforcement in MMC design, as well as the importance of the processing route to fabricate MMCs on a fine scale. The conclusions of the various areas of investigation demonstrated how damage in MMCs links together issues of process design, microstructural optimization and resultant mechanical properties of MMCs.
Keywords: Materials Science and Engineering; Materials Science and Engineering